(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The company’s achievements could be measured in the prism of human capital. Human capital adds substantial value to a business in a competitive market. Human capital in a company is associated with employment, employees are an essential resource, and at the same time, capital (asset). The human capital add value to a company in case it provides development, brings opportunity to innovative strategies, increases the efficiency of the work process and economic efficiency of the enterprise, uses market opportunities and neutralizes potential threats. Strategic human capital management should be in line with the business strategy by objectives and structure. The purpose of strategic human capital management is to determine its directions and methods to achieve the goals of the organization, and, increase its value. The strategy of human capital management requires: to take into account the needs and capabilities of all employees without exception (since they all have value – from the head of the company to the unskilled worker), the integration of human capital management with the business development strategy, sectoral and functional strategies. The theory and practice of management have developed many useful models to support strategic human capital management, with varying levels of complexity, the amount of knowledge required for their use, and the cost of implementation. An analysis of the models of strategic human capital management suggests that each enterprise can find the optimal ones from its point of view (Michigan model, Harvard model, Schuler human capital model, a model of acquisition and involvement (contractual), a model of all-outs in human capital, etc.). Сonsequently, a strategic human capital management should become a mandatory norm, and their integration with the business strategy is a prerequisite for strengthening its values.